Ozone therapy as a novel complementary therapeutic approach in refractory idiopathic granulomatous mastitis - Cabioglu, Neslihan; Trabulus, Didem Can; Emiroglu, Selman; Ozkurt, Enver; Yalcin, Nesli; Dinc, Nagehan; Tukenmez, Mustafa; Muslumanoglu, Mahmut; Igci, Abdullah; Ozmen, Vahit; Dinccag, Ahmet Sait; Guven, Yusuf Izzettin (Frontiers in Medicine, 2023)
Background: Autoimmunity may play a major role in the pathogenesis of idiopathic granulomatous mastitis (IGM). The therapeutic potential of ozone therapy has recently been shown in rheumatological diseases, and this study aimed to assess the clinical efficacy of ozone therapy (OT) in refractory IGM. Methods: Patients with biopsy-verified IGM and incomplete response after steroid therapy (n=47) between 2018 and 2021 were enrolled. Of these, 23 cases in cohort A had standard treatment with further steroid therapy (ST), and 24 were treated with systemic OT via autohemotherapy (AHT) in addition to steroid therapy (cohort B). Results: The median age was 33 years (range, 24-45). Patients in cohort B had a higher complete response rate after completion of a four-month ozone therapy than those in the ST-group (OT-group, 37.5% vs ST-group, 0%; p=0.002). At a median follow-up of 12 months (range, 12-35), the patients treated with OT had a lower one-year recurrence in the affected breast than cases in cohort A treated with ST (OT-group, 21% vs ST-group, 70%; p=0.001). No significant side effects were observed in patients in cohort B related to AHT. Furthermore, OT significantly decreased the total steroid treatment duration (median week of steroid use; 26 weeks in cohort A vs 12 weeks in cohort B; p=0.001). Conclusions: Systemic OT increases the complete response rate and decreases the duration of steroid treatment in patients with refractory IGM. Therefore, ozone therapy is an effective, well-tolerated, and safe novel complementary therapeutic modality.